2023
DOI: 10.1126/sciadv.adi5104
|View full text |Cite
|
Sign up to set email alerts
|

Broadband sensory networks with locally stored responsivities for neuromorphic machine vision

Guo-Xin Zhang,
Zhi-Cheng Zhang,
Xu-Dong Chen
et al.

Abstract: As the most promising candidates for the implementation of in-sensor computing, retinomorphic vision sensors can constitute built-in neural networks and directly implement multiply-and-accumulation operations using responsivities as the weights. However, existing retinomorphic vision sensors mainly use a sustained gate bias to maintain the responsivity due to its volatile nature. Here, we propose an ion-induced localized-field strategy to develop retinomorphic vision sensors with nonvolatile tunable responsivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Hence, in order to assess the device-to-device variability of the switching parameters as well as the reliability of the above results, a total of 36 independent and almost identical memory units (6 × 6 array) like that of D 1 were fabricated. It was found that out of these 36 memory units (cells), only 13 showed reliable WORM behavior with a significant memory window (∼10). Figure e shows the I – V response of these 13 memory units.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, in order to assess the device-to-device variability of the switching parameters as well as the reliability of the above results, a total of 36 independent and almost identical memory units (6 × 6 array) like that of D 1 were fabricated. It was found that out of these 36 memory units (cells), only 13 showed reliable WORM behavior with a significant memory window (∼10). Figure e shows the I – V response of these 13 memory units.…”
Section: Resultsmentioning
confidence: 99%
“…1−3 Conventional memory devices, which are mainly based on silicon, have several limitations such as downscaling, high power consumption, heat death, etc. 2 Moreover, performance enhancement of these devices has become excessively difficult in recent times. 4 Resistive switching memory devices based on various novel and easy-to-process materials can potentially serve as a solution to these problems.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, up to now, the computing results are generally obtained through simulation based on software. Therefore, achieving neuromorphic computing through extensive integration of arrays in hardware is a challenging journey that lies ahead [282].…”
Section: Challenge and Outlookmentioning
confidence: 99%
“…Nevertheless, due to the fact that optical artificial synapses exhibit a unidirectional response to light stimuli, both optical and electrical coconfigurations are necessary to accomplish reversible modulation of synaptic weights in most of the reported photoelectric synapses. ,, Moreover, optical stimulation often relates to the potentiation process, whereas electrical stimulation acts on the depression process. Alternatively, an optimal all-optical modulation of artificial synapses might eliminate the need for mixed optoelectronic signals, simplify the configuration of external stimuli, as well as greatly enhance the utilization of optical signals. The discussed all-optical controlled synaptic devices exhibit an increase and decrease in postsynaptic currents (PSCs) under different light stimuli, corresponding to positive photoconductance (PPC) and negative photoconductance (NPC), respectively. It is obvious that realizing a negative photoresponse is the primary obstacle to exhibiting a switchable bidirectional photoresponse in optoelectronic synapses.…”
Section: Introductionmentioning
confidence: 99%